2009 2nd Conference on Data Mining and Optimization 2009
DOI: 10.1109/dmo.2009.5341898
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Ant Colony systems for course timetabling problems

Abstract: The University Course Timetabling is a complex optimization Problem which is difficult to solve for optimality. It involves assigning lectures to a fixed number of timeslots and rooms; while satisfying some constraints. The goal is to construct a feasible timetable and satisfy soft constraints as much as possible. In this study, we apply two hybrids Ant Colony Systems, namely the Simulated Annealing with Ant Colony System (ACS-SA), and Tabu Search with Ant Colony System (ACS-TS) to solve the university course … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 23 publications
0
7
0
1
Order By: Relevance
“…In 2009, Jardat proposed a hybrid algorithm using an Ant Colony system with simulated annealing to solve the problem of university course timetable, which is regarded as a complex organization problem for which it is hard to find an optimal solution [17]. Socha et al (2002) developed a min-max ant system algorithm for the university course time tabling problem.…”
Section: Use Of the Pheromone By Ants Represents A Way Of Indirect Comentioning
confidence: 99%
“…In 2009, Jardat proposed a hybrid algorithm using an Ant Colony system with simulated annealing to solve the problem of university course timetable, which is regarded as a complex organization problem for which it is hard to find an optimal solution [17]. Socha et al (2002) developed a min-max ant system algorithm for the university course time tabling problem.…”
Section: Use Of the Pheromone By Ants Represents A Way Of Indirect Comentioning
confidence: 99%
“…The approaches that are commonly undertaken to solve the problems are metaheuristic algorithms which can be classified to population based algorithms such as Genetic Algorithm (Abdelhalim and El Khayat, 2016), Particle Swarm Optimization (Kennedy and Eberhart, 1995), Ant Colony Optimization (Socha et al, 2003) and local search algorithms such as Simulated Annealing (Bellio et al, 2016), Tabu Search (Lü and Hao, 2010), Great Deluge (Dueck, 1993) and Variable Neighborhood Search (Hansen and Mladenović, 1997) to name a few. The aforementioned algorithms possess their own sets of strength and weaknesses and in order to obtain a high quality solution, hybrid algorithms are proposed in order for the resultant algorithm to exhibit various strength derived from the initial algorithms such as hybrid cat swarm algorithms (Skoullis et al, 2016), hybrid particle swarm optimization (Shiau, 2011), hybrid ant colony systems (Ayob and Jaradat, 2009). This paper presents a hybrid Genetic Algorithm Neighborhood Search which integrates domain-specific exploitative properties of the Neighborhood Search into Genetic Algorithm to solve the CTP adopted from a real world example from a faculty in Universiti Teknologi Malaysia.…”
Section: Problem Backgroundmentioning
confidence: 99%
“…In one research work, this technique has demonstrated an excellent convergence when tested for uncovering low risk paths or routes in a sparse graph [40]. Hybridization between ACO with simulated annealing and ACO with tabu search with related to the course timetabling problem has produced good solutions compared to others methodologies [41]. In EAs, using S-metaheuristics strategy as a selection method has increased the algorithm performances in solving optimization problems.…”
Section: B Population Generation (Pg)mentioning
confidence: 99%